Easily obtained iodine and silver-iodine doped chitosan for medical and other applications - Anatoly M. Sklyar; Oksana V. Kalinkevich; Viktoriia N. Holubnycha; Aleksei N. Kalinkevich; Vadim D. Chivanov; Yana V. Trofimenko; Dmitry Sofronov; Vadim Starikov; Sergei N. Danilchenko (Carbohydrate Polymer Technologies and Applications, 2023)
The complex of polysaccharide chitosan with iodide acid was obtained and characterized. The possibility of obtaining iodine preparations in chitosan matrix with enhanced ability of chitosan to retain iodine is suggested. In this study to improve the stability of iodine, novel chitosan iodine complex was prepared by mixing chitosan with HI. Chitosan iodine complex was obtained as a solution, which can be treated to form bulk samples with open porosity and the enhanced ability to retain iodine. Silver-doped materials comprise insoluble silver iodide in amorphous or nanocrystalline form. The anti-bacterial as well as anti-fungal activity assessment of complexes of chitosan and iodine and chitosan and iodine with Ag has shown that chitosan iodide and chitosan iodide with Ag are more effective against fungi.